Five Go To Mystery Moor - Blyton, Enid (London Hodder Children's Books, 2004)
What is so mysterious about Mystery Morr? Do the unfriendly travellers know the answer? The Famous Five risk treacherous mists to follow them across the moor - but will the trail lead to danger?
Keywords: Children's Literature - Fiction : Adventure